Suppression of chloromethylphenol accumulation in wheat seedlings by uptake-induced phytotoxicity. (December 2016) - He, Anfei; Yuan, Jin; Jiang, Jing; Sheng, G. Daniel
Abstract: Uptake and its induced phytotoxicity are hypothesized to suppress overall organic chemical accumulation in plant. The extent and mechanism of suppression remain rather unknown. This study was conducted to evaluate, at both physiological and cellular levels, the phytotoxicity following plant exposure to an organic chemical and, in turn, the suppression of the organic chemical accumulation in the plant. Root uptake of 4-chloro-3-methylphenol (CMP) in wheat seedlings and subsequent CMP translocation to shoots were determined. Seedling transpiration and fatty acid (FA) profiles of cell membranes, along with malondialdehyde (MDA) generation and K + release in seedling tissues, were quantified. At CMP concentrations of 15, 45, and 60 mg L −1, CMP accumulations reached maxima of about 8.1, 24.7, 40.6 mg kg −1 in shoots, and 127.4, 187.2, and 244.3 mg kg −1 in roots, respectively. Most of these accumulations were lower than those estimated from partition-based models. Seedling transpiration was reduced by about 25% (15 mg L −1 ) and 60% (45 mg L −1 and 60 mg L −1 ). As a product of lipid peroxidation, MDA level in roots changed with exposure time following an "elevation-demotion" trend. This suggested that root cells suffered initial severe lipid peroxidation and gradually lost cell functions. This resulted in an increase in FA saturation degree of root cell membranes and hence damage to root cells. This was verified by enhanced K + release from root tissue. The "uptake-induced phytotoxicity-suppressed accumulation" cycle existed in plant uptake involving both physiological and cellular actions to maintain CMP accumulation in wheat seedlings lower than model estimation. Graphical abstract: Highlights: CMP accumulations in wheat seedlings are lower than estimated by partition model. CMP uptake reduces wheat seedling transpiration by up to 60%. CMP uptake increases fatty acid saturation degree and K release from cell membrane. Uptake and induced phytotoxicity together suppress CMP accumulations in seedlings.